Economic growth and structure in the Republic of Korea - Kuznets, Paul W. (New Haven : Yale University Press, 1977)
This book dwells on economic structure and growth, quantitative analysis of a national economy as an integral whole, comparative cross-sectional studies using data from a number of countries.
Includes index.
Bibliography: p. 221-232.
MF22/01/2019
Loan
Keywords: Economic conditions; Economic policy; Korea